PENGARUH KOMPENSASI, KEPUASAN KERJA, DAN STRES KERJA TERHADAP TURNOVER INTENTION - Erika Putri; Friztina Anisa (Universitas Ahmad Dahlan, 2022)
The success of an organization can be portrayed by the employee turnover intention rate each month. Employee turnover intention can be influenced by compensation, job satisfaction, and work stress. The purpose of this study is to test and analyze the relationship among compensation factors, job satisfaction, and work stress on employees at PT. Tanjung Kreasi Parquet Industri (TKPI). This study was conducted in a Quantitative research method with multiple regression analysis. The population of this study was all production employees. The sampling technique used was purposive sampling with a total of 201 employees. The results of the study prove that compensation and job satisfaction have a negative effect on turnover intention, while work stress has a positive effect on turnover intention.